Interface between psychoanalysis and speech language and hearing sciences: a literature review - Nascimento, Edinalva Neves; Ferreira, Dayse Mayara Oliveira; Santos, Flávia Rodrigues Dos; Silva, Nayra Neri Da; Oliveira, Sabrina Alves De; Carrer, Joyra Da Silva; Riato, Letícia Alvieri; Gozzer, Marina Mendes (ABRAMO Associação Brasileira de Motricidade Orofacial, 2017)
ABSTRACT The aim of this study was to verify the Brazilian and international scientific productions by correlating Speech Language and Hearing Sciences and Psychoanalysis. A literature review was performed using the databases BVS, Scielo, Scopus and PubMed. The used descriptors were “Fonoaudiologia”, “Psicanálise”, “Comunicação”, “Speech Therapy”, “Psychoanalysis” and “Communication”, identifying 65 full articles between the years 1980 and 2015. The analysis was performed using a “Protocol for article classification”. It was verified that Original Articles are the most published type, SCOPUS and BVS being the most common databases. There is a predominance of articles in the Portuguese language, followed by English, French and German. Several specialties of Speech Language and Hearing Sciences presented interface with Psychoanalysis, especially Language and Neuropsychology. The studies were published mainly in Psychology journals, also found in the area of audiology and interdisciplinary area. This review showed the psychoanalytic interference in speech language and hearing clinic, highlighting the need for further studies correlating both areas that may contribute to the work of these professionals and, consequently, enable an improvement in the quality of life of psychic subjects.

RESUMO O objetivo deste estudo foi verificar na literatura brasileira e internacional produções científicas correlacionando a Fonoaudiologia e a Psicanálise. Foi realizada revisão de literatura utilizando as bases de dados BVS, Scielo, Scopus e PubMed. Foram utilizados os descritores “Fonoaudiologia”, “Psicanálise”, “Comunicação”, “Speech Therapy”, “Psychoanalysis” e “Communication” e identificados 65 artigos completos entre os anos de 1980 a 2015. A análise foi realizada por meio de um “Protocolo de Classificação de Artigos”. Foi possível verificar que o tipo de trabalho mais publicado é o Artigo Original. Observou-se que SCOPUS e BVS foram as bases de dados mais comuns. Há um predomínio de artigos no idioma português, seguido por inglês, francês e alemão. Várias especialidades da Fonoaudiologia apresentaram interface com a psicanálise, especialmente, Linguagem e Neuropsicologia. Os trabalhos foram publicados principalmente em periódicos da Psicologia, sendo encontrados também na área da Fonoaudiologia e da Interdisciplinar. Este trabalho de revisão evidenciou a interferência psicanalítica na clínica fonoaudiológica, verificando a necessidade de mais estudos relacionando ambas as áreas que possam contribuir para a atuação desses profissionais e, consequentemente, possibilitar uma melhora na qualidade de vida do sujeito psíquico.
Interface entre a psicanálise e a fonoaudiologia: uma revisão da literatura
Keywords: Speech, Language and Hearing Sciences; Psychoanalysis; Communication; Fonoaudiologia; Psicanálise; Comunicação